Nexus between Aging and Health Expenditure: An Evidence from Nepal - Poudel, Tanka Mani; Gajurel, Ram Prasad (Journal of Innovation in Academia, 2023)
Nepal, like many countries, is currently experiencing a significant shift in its demographic landscape, characterized by a rapidly aging population. This study investigates the causal relationship between aging and healthcare expenditure in Nepal. To examine this causal connection, we employed a parsimonious VAR-based Wald test, Granger causality analysis, impulse response functions (IRFs), and forecast error variance decompositions using time series data from 2000 to 2020. The findings of the analysis reveal a substantial positive correlation between the proportion of elderly people and healthcare expenditure, indicating that as the population ages, healthcare costs and the demand for healthcare services tend to rise. The IRF analysis further confirmed that an innovation or shock in the aging index (AI) led to a subsequent increase in per capita health expenditure (HPC). Granger causality also reveals a unidirectional causal linkage from the aging index to per capita health expenditure. In addition, the study highlights the positive impact of aging on life expectancy in Nepal. These findings have important policy implications for Nepal. As the population continues to age, policymakers must allocate healthcare resources effectively, invest in geriatric care, and develop a robust healthcare infrastructure. Comprehensive long-term planning and strong social support systems are crucial to ensure the well-being of the elderly population and to mitigate the associated challenges.